AN ANALYSIS OF THEMES THAT BUILD ON C.S. LEWIS’S NOVEL " THE LION, THE WITCH, AND THE WARDROBE" - Balqis Majesty Wahana; Mhd. Johan (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2022)
ABSTRACT The aim of the study was to identify and analyze the literature. This research will focus on analyzing one of the intrinsic elements, namely theme. Thus, this study aims to analyze and describe the themes contained in the Novel “The Lion, The Witch, and The Wardrobe”, written by C. S. Lewis. The researcher chose to use a sociological approach in the process of literary criticism of this novel. The researcher will analyze the themes in the novel from a sociological perspective. Because literature itself is a reflection of society and social life is what gives birth to literature, therefore the two cannot be separated. According to Peck and Coyle, writers are moralists, and they observe and study the relationship between individuals and society and present their ideas about how people should behave but it would be too simplistic to say that the important thing about their novels is the message they convey (1986).